Faktor-Faktor Yang Berhubungan dengan PHBS - Novika, Novika; Sayati, Dewi; Murni, Nani Sari (Institut Citra Internasional, 2024)
The importance of raising awareness of Clean and Healthy Behavior (PHBS) in school-age children because schools have a strategic role and position in education and health promotion efforts. Efforts are needed to increase PHBS to prevent the risk of health problems at school. The purpose of this study was to find out the relationship between attitudes, actions, the role of peers, and the role of teachers towards PHBS in PKBM Sahabat Tahfizhul Quran. The research design is a quantitative analytic survey through a cross sectional approach. The population was 43 students in grades 3-6 elementary school. Sample is the total population. Data collection used a questionnaire and conducted interviews, then the data were analyzed using the Chi-square test. The results showed that most of the respondents had a bad attitude (72.1%), bad actions (69.8%), the role of peers was not good (51.2%), the role of the teacher was not good (55.8%), and PHBS is not good (72.1%). There is a relationship between attitude (p value 0.000, PR 7.750), action (p value 0.002, PR 4.615), the role of peers (p value 0.013, PR 5.328), and the teacher's role (p value 0.029, PR 3.789) with PHBS. The conclusion from this study is that there is a relationship between attitudes, actions, the role of peers, and the role of teachers towards PHBS in PKBM Sahabat Tahfizhul Quran. The researchers suggest increasing health promotion regarding PHBS in schools, monitoring the interaction of students with their peers, and increasing stimulation for teachers.